IDENTIFIKASI KARAKTERISTIK STRUKTUR PADA ARSITEKTUR TRADISIONAL NIAS UTARA (STUDI KASUS: RUMAH ADAT DESA TUMORI) - Ezra Syahfitrah Tanjung; Armelia; Fidyati (Rumoh Journal of Architecture, 2022)
Traditional architecture is an architectural style that emerges from the culture and beliefs of the people that continue to bepassed down to the next generation, through a building based on the culture of each tribe or ethnicity. Traditional houses inNias are built with different architectural styles, as well as the structural patterns of the village. The traditional architecture ofNorth Nias has a floor plan or oval walls and a curved roof, which is different from other forms of traditional Nias architecture.From this uniqueness, this research has the aim of identifying the structure of the building, seeking the potential of itsarchitectural characteristics, preserving the building and enriching knowledge about the traditional architecture of North Niasitself. The research method applied in this research is the ethnographic method as a research method that is included in thequalitative approach. The government, families who live in traditional houses, and the people of Nias are still not aware ofthe importance of preserving the traditional architecture of North Nias for their lives. Although the traditional houses of NorthNias are still numerous in quantity, the quality of the buildings has changed, ranging from almost uninhabitable to buildingsthat have undergone many transitions. The traditional architecture of Nias has a lot of potential from various aspects to bebeneficial for the future of Nias in terms of social and development. Therefore, studying, developing, and preserving thetraditional architecture of Nias is very important both to the people of the cloud and to the educated people